Emerging Trends of Virtual Laboratories in Vocational Education: A Bibliometric Analysis - Deris Oktageri; Sukardi; Usmeldi; Wagino Wagino; Hansi Effendi (Journal for Lesson and Learning Studies, 2025)
Research on virtual laboratories has shown significant growth but is still scattered across disciplines and approaches. This condition indicates the need for systematic mapping in the context of vocational education to understand the development and direction of current research. This study aims to analyze international publications related to virtual laboratories in vocational education, covering research trends, highest citations, leading countries, and relevant publication sources. A quantitative approach with bibliometric analysis was used on 163 of the Scopus database from 2010 - 2024. Data were collected using the keywords "virtual laboratory" and "vocational education." Data analysis was carried out using Microsoft Excel and VOSviewer to visualize the research findings. The results showed that the publication trend fluctuated annually but tended to increase. Journal of Physics: Conference Series, publication of Potkonjak, and Spain were identified as the most influential countries. Co-occurrence analysis revealed major clusters such as e-learning, engineering education, virtual laboratories, and students. Overlay visualization shows a shift in focus from distance learning to a more interactive and contextual technology-based pedagogical approach in vocational education. These findings provide implications for research collaboration, pedagogical integration, and the development of immersive virtual laboratories in vocational education.